2016
DOI: 10.1002/ejoc.201600884
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Nitroso Aldol Intramolecular Transesterification Cyclization Domino Reaction for Highly Effective Construction of Chiral Spirooxindoles

Abstract: A catalytic asymmetric nitroso aldol intramolecular transesterification cyclization domino reaction between a C3 alkyl ester substituted oxindole and nitrosobenzene for the construction of chiral spirooxindoles was achieved in the presence of a chiral bifunctional tertiary amine thiourea catalyst and water. Optically active spirooxindoles were obtained in moderate yields (up to 76 %) and excellent enantioselectivities (up to 95 % ee).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…[18] The same authors also recently used organocatalyst 6 for the construction of chiral spirooxindoles in good yields with high enantioselectivities (up to 95 % ee)b yp erforming the same reactionw ith C3 alkyl ester substituted oxindoles as the startingm aterial. [19] In contrast, Ta kemoto'st hiourea catalyst 7 was found to be slightly more selectivei nt he enantioselective hydroxyamination of unprotected oxindoles with nitrosobenzene (Scheme 6). [20] In both articles, the proposed transition states suggest ab ifunctional role of the catalyst by activating the reactiont hrough the tertiary amine and hydrogen bonding.…”
Section: Hydrogen-bonding Catalysismentioning
confidence: 96%
“…[18] The same authors also recently used organocatalyst 6 for the construction of chiral spirooxindoles in good yields with high enantioselectivities (up to 95 % ee)b yp erforming the same reactionw ith C3 alkyl ester substituted oxindoles as the startingm aterial. [19] In contrast, Ta kemoto'st hiourea catalyst 7 was found to be slightly more selectivei nt he enantioselective hydroxyamination of unprotected oxindoles with nitrosobenzene (Scheme 6). [20] In both articles, the proposed transition states suggest ab ifunctional role of the catalyst by activating the reactiont hrough the tertiary amine and hydrogen bonding.…”
Section: Hydrogen-bonding Catalysismentioning
confidence: 96%
“…Surprisingly, the utility of thiourea catalysts in nitroso aldol reactions remains far less developed. The scattered reports where bifunctional thiourea catalysis was found useful for this type of reaction, describe the hydroxyamination of oxindoles and β-ketoamides [49][50][51][52][53][54]. Recently, it has been shown that malonate derivatives such as malonate half thioesters and malonamides could be effectively used in various enantioselecive addition reactions [55][56][57][58][59][60].…”
Section: Introductionmentioning
confidence: 99%
“…2 Reactions involving the addition of isatin ketimines with various carbon-nucleophiles under Lewis acid or alkaline conditions 3 or the addition of C-3 aminooxindoles with alkenes promoted by organic bifunctional catalysts 4 have been investigated as straightforward methods to construct N-protected tetrasubstituted C-3 aminooxindoles (Scheme 1b). 5 Additionally, nitrogen-containing functional groups can be introduced into the C-3 position through the amination of 3-substituted 3-bromooxindoles or 3-substituted oxindoles with azodicarboxylates, 6 nitrosoarenes, 7 or N-electrophiles 8 (Scheme 1a). An alternative approach involves the palladium-catalyzed intramolecular cyclization of amide enolates, as reported by Kündig and Ley et al , which can provide N-protected privileged aminooxindole structures (Scheme 1c).…”
mentioning
confidence: 99%